THE EFFECTIVENESS OF IMPLEMENTING DISCHARGE PLANNING ON FAMILY KNOWLEDGE IN CARING FOR PATIENTS WITH CORONARY HEART DISEASE - Fismaleni, Menik; Dewi, Wan Nishfa; Hasneli, Yesi (Jurnal Keperawatan, 2025)
Discharge planning is a dynamic and systematic process of assessment, preparation, and coordination aimed at facilitating the supervision of health and social services before and after hospital discharge. This study aims to determine the effectiveness of discharge planning implementation on family knowledge in caring for patients with Coronary Heart Disease (CHD). A quasi-experimental design with a one-group pretest-posttest approach was used. The sample consisted of 27 respondents selected through accidental sampling based on inclusion criteria. The intervention involved providing educational material using a leaflet on family knowledge in caring for CHD patients. Knowledge was measured using a 25-item questionnaire. The results showed that most respondents were aged 45–54 years (48.1%), female (59.3%), had a high school education (59.3%), and had cared for CHD patients for less than one year (55.5%). In the bivariate analysis, the pretest scores indicated that 73.4% had moderate knowledge, while posttest scores revealed that 96.74% had good knowledge. These findings demonstrate that discharge planning significantly improves family knowledge in caring for CHD patients, which may help reduce recurrence and hospital readmission rates.